Exploring emergence in corporate sustainability - Maitland, Roger (Graduate School of Business (GSB), 2020)
As the impacts of climate change intensify, businesses are increasingly committing to ambitious sustainable development goals, yet an enduring disconnect remains between corporate sustainability activities and declining global environment and society. This study adopts a complexity view that reductionism associated with Newtonian thinking has played a key role in creating many of the sustainability issues now faced by humanity. This dissertation departs from the premise that sustainability needs to be integrated into an organisation and uses a complexity view to argue that corporate sustainability is a co-evolutionary process of emergence. Whilst many studies have examined how sustainability can be integrated into a business, less is known about corporate sustainability as an emergent process. To address the knowledge gap, this research answered three questions: (1) How does sustainability emerge in financial institutions? (2) What is the role of coherence in the emergence of sustainability? and (3) What conditions enable the emergence of sustainability? A mixed method sequential design was used. In the initial quantitative strand of the research, a holistic business assessment survey based on integral theory was implemented in two financial services organisations in Southern Africa. The results were analysed using self-organising maps and explored in narrative interviews in the subsequent qualitative strand of the research. The study makes three contributions to our understanding of emergence in corporate sustainability. First, by proposing four modes by which corporate sustainability is enacted; these elucidate how integral domains are enacted in corporate sustainability. Second, by clarifying the process of emergence by articulating how zones of coherence emerge between embodied and embedded dimensions. Third, by explaining how the shift to corporate sustainability occurs by means of four conditions. These contributions serve to advance our understanding of corporate sustainability as a fundamental shift in the functioning of an organisation towards coevolutionary self-organisation. It is recommended that corporate sustainability is holistically cultivated to support emergence and self-organisation, rather than being integrated through a linear process of change.